Characterization and genomic analyses of two newly isolated Morganella phages define distant members among Tevenvirinae and Autographivirinae subfamilies - Oliveira, Hugo (2017)
Morganella morganii is a common but frequent neglected environmental opportunistic pathogen which can cause deadly nosocomial infections. The increased number of multidrug-resistant M. morganii isolates motivates the search for alternative and effective antibacterials. We have isolated two novel obligatorily lytic M. morganii bacteriophages (vB_MmoM_MP1, vB_MmoP_MP2) and characterized them with respect to specificity, morphology, genome organization and phylogenetic relationships. MP1s dsDNA genome consists of 163,095bp and encodes 271 proteins, exhibiting low DNA (<40%) and protein (<70%) homology to other members of the Tevenvirinae. Its unique property is a >10kb chromosomal inversion that encompass the baseplate assembly and head outer capsid synthesis genes when compared to other T-even bacteriophages. MP2 has a dsDNA molecule with 39,394bp and encodes 55 proteins, presenting significant genomic (70%) and proteomic identity (86%) but only to Morganella bacteriophage MmP1. MP1 and MP2 are then novel members of Tevenvirinae and Autographivirinae, respectively, but differ significantly from other tailed bacteriophages of these subfamilies to warrant proposing new genera. Both bacteriophages together could propagate in 23 of 27M. morganii clinical isolates of different origin and antibiotic resistance profiles, making them suitable for further studies on a development of bacteriophage cocktail for potential therapeutic applications.